2018
DOI: 10.5696/2156-9614-8.18.180605
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment and Blood Lead Levels of Children in Owino Uhuru and Bangladesh Settlements in Kenya

Abstract: Background.Lead exposure is linked to intellectual disability and anemia in children. The United States Centers for Disease Control and Prevention (CDC) recommends biomonitoring of blood lead levels (BLLs) in children with BLL ≥5 μg/dL and chelation therapy for those with BLL ≥45 μg/dL.Objectives.This study aimed to determine blood and environmental lead levels and risk factors associated with elevated BLL among children from Owino Uhuru and Bangladesh settlements in Mombasa County, Kenya.Methods.The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…What we do know from assimilating the information in these two papers is that there is a historic lead smelter in Owino Uhuru that likely contributed to the elevated BLLs observed by Etiang et al1 Additionally, we know that levels of lead in soil vary significantly in these communities and it appears it is entering residential dwellings. What still needs to be determined is the precise exposure source and pathway.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…What we do know from assimilating the information in these two papers is that there is a historic lead smelter in Owino Uhuru that likely contributed to the elevated BLLs observed by Etiang et al1 Additionally, we know that levels of lead in soil vary significantly in these communities and it appears it is entering residential dwellings. What still needs to be determined is the precise exposure source and pathway.…”
mentioning
confidence: 90%
“…In June 2018, this journal published the work of Etiang et al1 The authors took childhood blood lead level (BLL) measurements (n=130) as well as limited samples of lead in soil (n=8), dust (n=7) and drinking water (n=15) from 130 households. They concluded that, among other activities, “ The high lead level of soil in Owino Uhuru (neighborhood) illustrates the need for coordinated efforts to remediate the environment .”1 They furthermore stated that “ This requires removal of the first several inches of soil and replacing with clean fill, which may necessitate the removal of children from their homes until the environment is confirmed to be safe .”1…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Following the closure of the facility in 2015, a study of environmental lead concentrations and community BLLs was carried out jointly by the Kenya Ministry of Health and the CDC. The study found a geometric mean surface soil lead concentration in the community of 146.5 mg/kg (geometric standard deviation (GSD): 5.2) and dust lead loadings in homes of 1.5 μg/ft 2 (GSD: 12.3) 49. These results were significantly below applicable United States Environmental Protection Agency (USEPA) screening levels for residential soil and household dust of 400 mg/kg and 40 μg/ft 2 , respectively 50.…”
Section: Introductionmentioning
confidence: 99%